Building complex carbon skeletons with ethynyl[2.2]paracyclophanes - Dix, Ina; Bondarenko, Lidija; Jones, Peter G.; Oeser, Thomas; Hopf, Henning (Beilstein journal of organic chemistry, 2014)
Beilstein Journal of Organic Chemistry